The main types of mental information processing: a systematic structural method - Tsupikova, Elena (2021)
The article describes the main types of mental information processing in the context of a systematic structural method. The author analyses the semantic theories of information. The author reviews the mechanisms of information processing and its qualitative properties. The article describes the mechanism of textual presupposition accommodation.